Don't go in the basement - Suzanne, Jamie; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1997)
When the twins started a house-sitting service, they never imagined their first client would be the school principal. They decide to do some snooping while they're there in hope of finding some juicy gossip, but they find more than they bargained for: a butcher knife in the hall closet, a long lock of hair in the dresser, and something else among the cobwebs of the dark, damp basement.
Keywords: Twins stories; Teenagers; Mystery fiction